The impact of coastal infrastructure improvements on economic growth: Evidence from Barbados - Leonardo Corral; Maja Schling; Cassandra Rogers; Janice Cumberbatch; Fabian Hinds; Naijun Zhou; Michele Lemay (Inter-American Development Bank (IDB), 2016)
This paper presents the first rigorous impact evaluation of a shoreline stabilization program in Barbados and attempts to assess whether shoreline stabilization investments indeed have beneficial effects on medium-term economic growth in Small Island Developing States through stimulating tourism demand and real estate development. The analysis relies on a carefully designed geographic information systems (GIS) dataset, which comprises extensive panel data from Barbados' touristic West and South Coasts on key infrastructure, beach characteristics, and real estate activity, as well as remotely-sensed luminosity data as a proxy of economic growth. The synthetic control method is employed to construct a counterfactual from a combination of all control beach sites and subsequently estimate program impact on per capita luminosity as a proxy for GDP p.c.. Results indicate that even in the first three years after treatment, economic effects are positive and indicate a strong positive trend. This suggests that shoreline stabilization works may not only help preserve fragile ecological conditions, but further lead to sustainable growth in the local economy.
Keywords: O44; Q54; D04; N56; 330; Shoreline Stabilization; Economic Growth; Luminosity; Synthetic Control; Barbados